Ignoring poverty in the U.S. : the corporate takeover of public education - Thomas, P. L. 1961- (Emerald Publishing Limited : Information Age Publishing, Inc., 2012)
Ignoring Poverty in the U.S.: The Corporate Takeover of Public Education examines the divide between a commitment to public education and our cultural myths and more powerful commitment to consumerism and corporate America. The book addresses poverty in the context of the following: the historical and conflicting purposes in public education--how schools became positivistic/behavioral in our quest to produce workers for industry; the accountability era--how A Nation at Risk through NCLB have served corporate interest in dismantling public education and dissolving teachers unions; the media and misinformation about education; charter schools as political/corporate compromise masking poverty; demonizing schools and scapegoating teachers--from misusing the SAT to VAM evaluations of teachers; rethinking the purpose of schools--shifting from schools as social saviors to addressing poverty so that public education can fulfill its purpose of empowering everyone in a democracy; and reframing how we view people living in poverty--rejecting deficit views of people living in poverty and students struggling in school under the weight of lives in poverty.This work is intended to confront the growing misinformation about the interplay among poverty, public schools, and what schools can accomplish while political and corporate leadership push agendas aimed at replacing public education with alternatives such as charter schools. The audience for the publication includes educators, educational reformers, politicians, and any member of the wider public interested in public education.